2013
DOI: 10.1186/1471-2369-14-22
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23 is associated with carotid artery calcification in chronic kidney disease patients not undergoing dialysis: a cross-sectional study

Abstract: BackgroundFibroblast growth factor 23 (FGF23) is an important hormone in the regulation of phosphate metabolism. It is unclear whether FGF23 is associated with carotid artery calcification (CAAC) in predialysis patients. The present study aimed to clarify the relationship between FGF23 and CAAC in patients with chronic kidney disease (CKD) who were not on dialysis.MethodsOne-hundred ninety-five predialysis CKD patients were enrolled in this cross-sectional study. CAAC was assessed using multidetector computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 42 publications
1
28
1
1
Order By: Relevance
“…37 An inverse relationship between CAC prevalence and BMD by DXA has also been shown in patients who are osteoporotic with normal kidney function and patients with HIV or metabolic syndrome. [38][39][40][41] In this study, a positive correlation was found between CAC SQRVand FGF23, which is in agreement with several published reports on vascular calcifications [42][43][44][45][46] but not in keeping with another report on patients with CKD not on dialysis. 29 Baseline FGF23 remained an independent predictor for baseline CAC after multivariable adjustment for age, CAD, diabetes, dialysis vintage, and BMD.…”
Section: Discussionsupporting
confidence: 92%
“…37 An inverse relationship between CAC prevalence and BMD by DXA has also been shown in patients who are osteoporotic with normal kidney function and patients with HIV or metabolic syndrome. [38][39][40][41] In this study, a positive correlation was found between CAC SQRVand FGF23, which is in agreement with several published reports on vascular calcifications [42][43][44][45][46] but not in keeping with another report on patients with CKD not on dialysis. 29 Baseline FGF23 remained an independent predictor for baseline CAC after multivariable adjustment for age, CAD, diabetes, dialysis vintage, and BMD.…”
Section: Discussionsupporting
confidence: 92%
“…Treatment with vitamin D analogues of calcitriol, frequently used in CKD patients, also contributes to increased FGF23 concentrations [88,89]. Elevated FGF23 levels have been associated with increased mortality in patients with end stage renal disease [90] and direct detrimental effects on the cardiovascular system [91], endothelial dysfunction, arterial stiffness [92] and left ventricular hypertrophy [93] have been implicated.…”
Section: The Skeleton and Mineral Homeostasismentioning
confidence: 98%
“…Unlike phosphate, however, the effect of FGF23 on arterial calcification is associated with the degree of kidney function. FGF23 is not associated with coronary artery calcification in individuals with normal renal function (94), and there are conflicting reports of the association in patients with CKD predialysis (62,95). However, FGF23 does correlate with peripheral and aortic calcification in patients on hemodialysis (96,97).…”
Section: Fgf23 and Klotho In Cardiovascular Diseasementioning
confidence: 99%